2016
DOI: 10.14419/ijans.v5i1.5686
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the nursing intervention program on feeling of burden and coping among caregivers of children with epilepsy

Abstract: Epilepsy is one of the most common pediatric neurological disorders, which have negative psychological, emotional, and physical consequences of providing care. Nursing intervention is a key element of managing these patients and their families in order to reduce feelings of burden and enhancing coping among caregivers. Aim: To evaluate the effectiveness of nursing intervention on a feeling of burden and coping among caregivers of children with epilepsy. Design: A quasi-experimental design (one group pretest-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Table 3 shows the association between some of the socio-demographic and overall level of caregivers' coping and indicates the presence of highly significant Acute leukemia in children like other chronic diseases has a significant physical and psychosocial effect on the family members and caregivers leading to poor coping with this condition. Regarding the sociodemographic characteristics, the highest percentage of the study caregivers were in their thirties (the mean age of 36.53 ± 7.53 years), which agrees with the result of a previous, quasi-experimental study conducted in Egypt with 80 caregivers' of children with epilepsy that found the mean age score was 37.21±5.22 years [10]. The result of this study indicated that the highest percentage of caregivers caring for leukemic children were mothers, which is consistent with the result of a descriptive study conducted by Hasan et al in Erbil (2012), which assessed the caregivers' home care for adolescent leukemia patients and found that most of the caregivers (71.3%) were the patients' mothers [3].Furthermore, the study found that the caregivers of leukemic children were mostly secondary school graduates or illiterate and the majority were living in urban areas.…”
Section: Family History Of Cancersupporting
confidence: 88%
See 1 more Smart Citation
“…Table 3 shows the association between some of the socio-demographic and overall level of caregivers' coping and indicates the presence of highly significant Acute leukemia in children like other chronic diseases has a significant physical and psychosocial effect on the family members and caregivers leading to poor coping with this condition. Regarding the sociodemographic characteristics, the highest percentage of the study caregivers were in their thirties (the mean age of 36.53 ± 7.53 years), which agrees with the result of a previous, quasi-experimental study conducted in Egypt with 80 caregivers' of children with epilepsy that found the mean age score was 37.21±5.22 years [10]. The result of this study indicated that the highest percentage of caregivers caring for leukemic children were mothers, which is consistent with the result of a descriptive study conducted by Hasan et al in Erbil (2012), which assessed the caregivers' home care for adolescent leukemia patients and found that most of the caregivers (71.3%) were the patients' mothers [3].Furthermore, the study found that the caregivers of leukemic children were mostly secondary school graduates or illiterate and the majority were living in urban areas.…”
Section: Family History Of Cancersupporting
confidence: 88%
“…This validated instrument was designed to assess parents' or caregivers' appraisal of behaviors currently in use to manage family life when they have chronically ill children. The tool was previously modified by El-Malky in 2016 [10]. The tool was submitted to a panel of eleven experts in different fields of nursing and medicine to assess the content of the questionnaire for its clarity, relevance, and adequacy.…”
mentioning
confidence: 99%
“…The outcomes of this result agree with the study done by Hashemi, et al, (13) on (72) parents included in the study, mention that the participants in this study was primary to high school education (69.4%). Another study with a convenience sample of 80 caregivers conducted by El Malky et al, (14) at the outpatient department at the health insurance institute in Shebin El-Kom district, Menoufia Governorate in Egypt. The finding of this study represent that the majority of participants (75%) was not working.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of caregiver burden has been confirmed by Palli et al through interventions such as psycho-educational training (28), which seems to increase the mental, physical, and social health of parents due to the positive impact of the program on the level of their knowledge and attitude. The results of a study conducted by El-Malky et al (2016) in Egypt " showed that training of families could reduce the caregiver burden in controlling epileptic seizures, the necessity of adherence to treatment, how to deal with unpredictable behaviors of patients, dealing with stigma, managing stress and improving adaptation strategies (10).…”
Section: Discussionmentioning
confidence: 99%
“…Many caregivers of patients with epilepsy report that they do not have sufficient skills and knowledge for longterm care of their patients, which indicates the importance of training them by healthcare providers (19,20) such as some nurses who are responsible for training families of patients with epilepsy (4,10,15). If family psychosocial training provides accurate information about illness and treatment, it can reduce the negative attitude and make family feel better, and, in turn, control the negative emotions expressed (7).…”
Section: Introductionmentioning
confidence: 99%